Frugivores enhance potential carbon recovery in fragmented landscapes - Bello, Carolina (2024)
Forest restoration is fundamental to overcoming biodiversity crises and climate change. In tropical forests, animals can improve forest recovery as they disperse >70% of tree species. However, representing animals in restoration and climate change policies remains challenging because a quantitative assessment of their contribution to forest and carbon recovery is lacking. Here we used individual-based models to assess frugivore-mediated seed rain in open areas along a fragmentation gradient. Movements of large birds were limited in landscapes with <40% forest cover, although small birds continued to disperse seeds. Large birds disperse seeds of late-successional species with higher carbon storage potential. Their restricted movement therefore reduced potential biomass in future forests by 38%. Maintaining forest cover >40% is essential to optimizing animals’ contribution to restoration success. Active restoration (for example, planting trees) is required in more fragmented landscapes to achieve carbon and biodiversity targets.